Nursing Intervention in Children with Diarrhea: A Case Study - Titihalawa, Elly Marce; Kurniasih, Dwi; Panggus, Florida Listavia (Journal of Maternal and Child Health, 2021)
Background: Diarrhea or gastroenteritis is a condition as watery bowel movements more than three times a day for two consecutive days, which may or may not be related to pathological conditions. Diarrhea can occur in all age groups, both toddlers, children and adults with various social groups. Diarrhea is the second leading cause of death in children under five years and almost 1.7 billion cases of diarrhea occur in children with a mortality rate of around 525,000. This study aims to describe the application of knowledge and practice of nursing care in children with diarrhea with the problem of risk of hypovolemia due to active fluid loss. Subjects and Method: This was a qualitative study with a phenomenological approach. The study was conducted at the Pontianak Level II Government Hospital, for 2 weeks. The sample used in this study were 4 key informants from 6 planned respondents and 3 triangulated informants. The key informants are nurses who work in the child care room, while the 3 triangulation informants are the client's family. The study variables were optimizing nursing interventions and diarrhea in children. Data collection was carried out by structured and direct interviews using a tape recorder before it was analyzed. Results: This study identified several themes such as meeting fluid needs, decreasing body temperature, and preventing damage to skin integrity, but in the case of diarrhea in children, meeting fluid needs is the nurse's main intervention that must be done in overcoming hypovolemia without forgetting the involvement of parents. Conclusion: Meeting fluid needs is a nurse's top priority in providing nursing care to diarrhea patients to prevent hypovolemia.